ChemInform Abstract: Ynamide Carbopalladation: A Flexible Route to Mono‐, Bi‐ and Tricyclic Azacycles. Issue 2 (23rd December 2015) - Campbell, Craig D.; Greenaway, Rebecca L.; Holton, Oliver T.; Walker, P. Ross; Chapman, Helen A.; Russell, C. Adam; Carr, Greg; Thomson, Amber L.; Anderson, Edward A.
Abstract: A plenty of azacycles is obtained by a cascade sequence of carbopalladation followed by cross‐coupling/electrocyclization, or reduction processes.